Risk-benefit assessment of onlay and retrorectus mesh augmentation for incisional hernia prophylaxis: A secondary analysis from network meta-analysis. (August 2021) - Tansawet, Amarit; Numthavaj, Pawin; Techapongsatorn, Suphakarn; McKay, Gareth; Attia, John; Pattanaprateep, Oraluck; Thakkinstian, Ammarin
Abstract: Background: Mesh augmentation has proved efficacious for the prevention of incisional hernia (IH). A recent network meta-analysis (NMA) identified onlay and retrorectus mesh (OM and RM) as the most effective therapeutic options, but the risk of surgical site infection (SSI) and other complications require additional consideration. Methods: The NMA generated pooled risk differences (RD) for the benefits of reducing IH and the risk of SSI and composite seroma/hematoma (CSH) for use in Monte-Carlo data simulations with 1000 replications. Mean incremental risk-benefit ratios (IRBR), i.e., the ratio of incremental risk (or RD) and incremental benefit, and 95% confidence intervals (95% CI) were estimated with a probability of risk-benefits (PRB) across risk-benefit acceptability thresholds from the acceptability curves generated. Results: The RDs of IH were 0.237 and 0.201 lower in OM and RM than primary suture closure, compared to 0.027 and −0.001 for SSI. IRBRs (95% CI) for SSI risk were −0.118 (−0.124, −0.112) and 0.006 (−0.002, 0.013) for OM and RM, respectively. PRBs were much higher in RM than OM, especially at low acceptability thresholds of 0.05 and 0.1. IRBRs (95% CI) for CSH were −0.388 (−0.395, −0.381) and −0.105 (−0.111, −0.100) for OM and RM, respectively. RM yielded a PRB of 0.87 at an acceptability threshold of 0.2, in contrast to OM, which did not. Conclusion: Overall, RM offered improved benefit in IH prophylaxis over the risk of complications relative to OM and appeared to be the preferred treatment option for this indication. Highlights: Onlay mesh (OM) augmentation is more efficacious than retrorectus mesh (RM) for incisional hernia prophylaxis. RM is more risk-beneficial than OM, when surgical site infection and combined seroma/hematoma are considered. RM should be recommended for prophylaxis indication considering safety.